ANALISIS STRATEGI UNTUK PT XL AXIATA TBK - Hidayat, Angela Nathania (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2024)
This research analyzes and formulates the corporate strategy of PT XL Axiata Tbk, one of the largest telecommunications companies in Indonesia, in the face of intense industry competition. This research uses internal analysis, external analysis, SWOT, GRAND, IE, and SPACE matrixes for strategy generation and decision. The result of the study shows that the main strategies of PT XL Axiata Tbk are product development, market penetration, and horizontal integration. This paper also presents a strategy implementation plan for the next 5 years and KPIs along with risks and risk mitigation. The study findings are expected to provide insights for decision-makers at PT XL Axiata Tbk and contribute to the literature on business strategy in the Indonesian telecommunications industry. Keywords : Strategy, Strategy Formulation, PT Ramayana Lestari Sentosa, Tbk